Two‐year safety and effectiveness of the platinum chromium everolimus‐eluting stent for the treatment of small vessels and longer lesions. Issue 2 (4th July 2014) - Teirstein, Paul S.; Meredith, Ian T.; Feldman, Robert L.; Rabinowitz, A. Charles; Cannon, Louis A.; Lee, Tommy C.; Dens, Joseph; Dubois, Christophe L.; Mooney, Michael R.; Pompili, Vincent J.; Saito, Shigeru; Allocco, Dominic J.; et al.
<x xml:space="preserve">Abstract</x> Objectives To report 1‐ and 2‐year clinical outcomes of patients receiving platinum chromium everolimus‐eluting stents (PtCr‐EES) in the prospective, single‐arm PLATINUM small vessel (SV) and long lesion (LL) studies. Background Small vessel diameter and long lesion length are independently associated with increased risk of adverse cardiac events after drug‐eluting stent implantation. Methods The PLATINUM SV study enrolled 94 patients with coronary artery lesions in vessels ≥2.25 mm to <2.50 mm in diameter and ≤28 mm in length. The PLATINUM LL study enrolled 102 patients with lesions >24 to ≤34 mm long in vessels ≥2.50 to ≤4.25 mm in diameter. The primary endpoint for both studies was target lesion failure (TLF) at 1 year compared to a prespecified performance goal based on outcomes with the TAXUS Express paclitaxel‐eluting stent in small vessels and long lesions. Results One‐year TLF rates with the PtCr‐EES were significantly (P < 0.001) lower than the predetermined performance goals: 2.4% versus 21.1% in the SV cohort and 3.2% versus 19.4% in the LL cohort. Cumulative rates of TLF to 2 years were 4.7% in the SV cohort and 8.8% in the LL cohort. No myocardial infarction or ARC definite/probable stent thromboses occurred in either cohort through 2‐year follow‐up. Conclusions The clinical efficacy and safety outcomes observed in these small vessel and long lesion cohorts support the use of the PtCr‐EES in the treatment of small diameter vessels and long lesions. © 2014 Wiley Periodicals, Inc.